Alterações qualitativas em contratos de obra pública e a teoria econômica dos contratos incompletos : é possível construir um avião em pleno voo? - Uryn, André (2016)
It is not from today that the country witnesses the discovery of countless cases of diversion of public money or even mismanagement of public works contracts, which brings forth, in addition to serious losses to the Public Treasury, damage to society, often deprived of the utility which would be provided by what was agreed. This behavior is usually caused by engineering projects which may be considered as mere works of fiction, for they do not represent the correct effort for the execution of the asset one intends to build. Law nº 8,666/93 allows for bidding processes based on a basic design building project, still incomplete, which, according to current Brazilian thought trends, from doctrine, controlling bodies, the legislative power or even the media, is in fact a serious problem to be faced, as its acceptance makes room for amendments, understood as the great villains of public works. For this reason, the Federal Court of Accounts of Brazil (TCU) has been deciding towards strongly restricting the possibility of contract amendments and, moreover, it has proposed bills before the National Congress aimed at extinguishing undertakings for unit price, a type of contract in which the project risk, still without the necessary definitions, ends up being borne by the contracting administration, in charge of its conception, not by its executor. However, in the case of complex infrastructure works, one should verify whether this stance, which seeks to put an end to the public administrator’s margin of decision-making regarding project completion, and, therefore, of the contract, deserves to be rethought, not with purpose of allowing for recurring damages, but rather towards better planning of state actions. This so happens because, in these cases, the search for all data needed for preparing the project to be ultimately performed is either too expensive or simply not feasible. Thus, design-build would be more efficient, as contemplated in the Brazilian law of differentiated regime for contracting (RDC), in which the risks may be allocated to the contractor. However, as restrictions exist, this path is not always feasible. In this order of ideas, one should find a solution so that the traditional public works contract overcomes its serious incentive problems. The present work proposition is the regulation, to be promoted before the new infrastructure law branch, that promotes a transparent and empirical decision-making process and confers legal certainty and widespread knowledge by society, as well as free access to the controlling bodies, based not only on legal criteria as well as economic and technical.